Trends in smoking-attributable mortality in Spain: 1990–2018. (17th November 2022) - Rey-Brandariz, Julia; Pérez-Ríos, Mónica; Santiago-Pérez, María Isolina; Galán, Iñaki; Schiaffino, Anna; Varela-Lema, Leonor; Montes, Agustín; López-Vizcaíno, María Esther; Giraldo-Osorio, Alexandra; Candal-Pedreira, Cristina; Ruano-Ravina, Alberto
Abstract: Background: This study sought to analyse the trend in smoking-attributable mortality (SAM) in Spain among the population aged ≥35 years across the period 1990–2018. Methods: SAM was estimated by applying a prevalence-independent method, which uses lung cancer (LC) mortality as a proxy of tobacco consumption. We sourced observed mortality from the National Institute of Statistics (Spain), LC mortality rates in smokers and never smokers from the Cancer Prevention Study I–II, and relative risks from 5 US cohorts. Estimates of annual SAM by cause of death, sex and age are shown, along with crude and annual standardised SAM rates. The trend in standardised all-cause and LC rates was analysed using a joinpoint regression model. Results: Tobacco caused 1 717 150 deaths in Spain in the period 1990–2018. Among men, cancers replaced cardiovascular diseases–diabetes mellitus (CVD–DM) as the leading group of tobacco-related cause of death in 1994. Among women, CVD–DM remained the leading cause of death throughout the period. Trend analysis of standardised SAM rates due to all causes and LC showed a decrease in men and an increase in women. Conclusions: The tobacco epidemic in Spain across the period 1990–2018 has had an important impact on mortality and has evolved differently in both genders. SAM is expected to increase dramatically in women in the coming years. SAM data highlight the importance of including a gender perspective in SAM analyses, in designing more effective and comprehensive public health interventions and in developing gender-specific tobacco control policies to curb tobacco consumption.